Synthesis of a Ni(OH)2@Cu2Se hetero-nanocage by ion exchange for advanced glucose sensing in serum and beverages. (1st September 2023) - Yang, Tong; Zhang, Wenna; Wu, Jiashun; Zhu, Siwei; Wang, Du; Lei, Cheng; Zhao, Yan
Highlights: Ni(OH)2 nanocage coupling with Cu2 Se nanosheet was first used in glucose sensing. Ni(OH)2 -Cu2 Se heterostructure remarkably favored fast electron collection/transfer. The hetero-nanocage had good structural robustness enabling long-term sensing. The prepared catalyst can sensitively detect glucose in serum and beverage samples. Abstract: Cu2 Se nanosheets were coated on the surface of Ni(OH)2 nanocages (NCs) by ion exchange driven by selenium incorporation. The resulting Ni(OH)2 @Cu2 Se hollow heterostructures (Ni(OH)2 @Cu2 Se HHSs) showed high electrical conductivity and electrocatalytic activities derived from the synergistic effects of Ni/Cu phases. These structures enhanced glucose adsorption abilities, confirmed by density function theory (DFT) calculations, and the robustness of the integrated nano-electrocatalyst. Remarkably, Ni(OH)2 @Cu2 Se HHSs modified electrodes excited excellent glucose sensing behavior with a wide linear range (0.001–7.5 mM), a sensitivity up to 2420.4 Μa mM −1 cm 2, a low limit of detection (LOD, 0.15 μM), and fast response (less 2 s). Furthermore, Ni(OH)2 @Cu2 Se HHSs competently analyzed glucose in serum and beverages with good recoveries ranging from 94.4 to 103.6%. Integrating copper selenide and Ni-based materials as 3D hollow heterostructures expands the selection of electrocatalysts for sensitive glucose detection in food and biological samples.